The impact of rehabilitation using removable partial dentures and functionally orientated treatment on oral health-related quality of life: A randomised controlled clinical trial. Issue 1 (January 2015) - McKenna, Gerald; Allen, P. Finbarr; O'Mahony, Denis; Cronin, Michael; DaMata, Cristiane; Woods, Noel
Abstract Objectives This study aimed to compare two different tooth replacement strategies for partially dentate older patients; namely functionally orientated treatment according to the principles of the shortened dental arch (SDA) and conventional treatment using removable partial dentures (RPDs) using a randomised controlled clinical trial. The primary outcome measure for this study was impact on oral health-related quality of life (OHRQoL) measured using the short form of the oral health impact profile (OHIP-14). Methods Patients aged 65 years and older were randomly allocated to two different treatment groups: the RPD group and the SDA group. For the RPD group each patient was restored to complete arches with cobalt–chromium RPDs used to replace missing teeth. For the SDA group, patients were restored to a premolar occlusion of 10 occluding pairs of natural and replacement teeth using resin bonded bridgework (RBB). OHRQoL was measured using the OHIP-14 questionnaire administered at baseline, 1 month, 6 months and 12 months after treatment intervention. Results In total, 89 patients completed the RCT: 44 from the RPD group and 45 from the SDA group. Analysis using a mixed model of covariance (ANCOVA) illustrated that treatment according to the SDA concept resulted in significantly better mean OHIP-14 scores compared with RPD treatment (p < 0.05). This result was replicated in both treatment centres used in the study. Conclusions In terms of impact on OHRQoL, treatment based on the SDA concept achieved significantly better results than that based on RPDs 12 months after treatment intervention (trial registration no. ISRCTN26302774). Clinical significance Functionally orientated treatment delivery resulted in significantly better outcomes compared to removable dentures in terms of impact on OHRQoL.